The impact of regulatory T cells on the graft-versus-leukemia effect - Pacini, Carolina P.; Soares, Maria V. D.; Lacerda, João F. (Frontiers in Immunology, 2024)
Allogeneic Hematopoietic Stem Cell Transplantation (allo-HSCT) is the only curative therapy for many hematologic malignancies, whereby the Graft-versus-Leukaemia (GVL) effect plays a pivotal role in controlling relapse. However, the success of GVL is hindered by Graft-versus-Host Disease (GVHD), where donor T cells attack healthy tissues in the recipient. The ability of natural regulatory T cells (Treg) to suppress immune responses has been exploited as a therapeutical option against GVHD. Still, it is crucial to evaluate if the ability of Treg to suppress GVHD does not compromise the benefits of GVL. Initial studies in animal models suggest that Treg can attenuate GVHD while preserving GVL, but results vary according to tumour type. Human trials using Treg as GVHD prophylaxis or treatment show promising results, emphasizing the importance of infusion timing and Treg/Tcon ratios. In this review, we discuss strategies that can be used aiming to enhance GVL post-Treg infusion and the proposed mechanisms for the maintenance of the GVL effect upon the adoptive Treg transfer. In order to optimize the therapeutic outcomes of Treg administration in allo-HSCT, future efforts should focus on refining Treg sources for infusion and evaluating their specificity for antigens mediating GVHD while preserving GVL responses.